Using benchtop NMR spectroscopy as an online non-invasive in vivo lipid sensor for microalgae cultivated in photobioreactors. (June 2020) - Bouillaud, Dylan; Drouin, Delphine; Charrier, Benoît; Jacquemmoz, Corentin; Farjon, Jonathan; Giraudeau, Patrick; Gonçalves, Olivier
Graphical abstract: Highlights: Compact NMR spectroscopy as an online non-invasive microalgae in vivo lipid sensor. The NMR signal is quantitative when calibrated with total lipid reference method. The NMR performance is compatible with the bioprocess operating conditions. Lipid productivities are measured in real-time for real-time optimization purposes. Abstract: The production of lipids by microalgae is widely studied, especially to find the best bioprocess operating conditions and optimize the productivity of the targeted product. In this context, being able to monitor online the evolution of the lipid concentration is a great advantage regarding the control and/or the optimization of the production. Yet, most non-invasive analyses hit a brick wall on the interference of the lipid signal with the ubiquitous water of the culture medium. This article shows how a compact NMR spectrometer connected to a photobioreactor can circumvent this drawback and measure, in real-time and in a non-invasive manner, the total lipid concentration, and that directly on the entire cells grown in their culture medium. The water signal could be enough-selectively removed using the W5 version of the WATERGATE pulse sequence. The NMR signal nicely correlates (R² > 0.99) with the offline FAME (Fatty Acid Methyl Ester) total lipid analysis as performed by GC-FID (Gas Chromatography coupled to Flame Ionization Detector) within limits of detection and quantification of respectively 9 and 30 mg.L −1 . The lipid specific signal appears also quite robust regarding the dissolved dioxygen, making the benchtop NMR spectroscopy an appropriate universal device for the online monitoring of lipids produced in bioprocesses.